134k views
3 votes
What is the correct inverse function for f(x)=ln(3x)?

2 Answers

7 votes

Let y = f(x)

y = ln(3x)

Exchange place with x and y.

x = ln(3y)

Solve for y.

y = (e^x)/3

Replace y with the inverse notation.

f^(-1) x = (e^x)/3

Done.



User John Difool
by
6.1k points
0 votes

Answer:


f^(-1)(x)= (e^x)/(3)

Explanation:

f(x)= ln(3x)

First we replace f(x) with y

y=ln(3x)

Now , interchange the variables x and y

x= ln(3y)

Solve the equation for y

We know ln has base 'e'

e^x = 3y

divide by 3 on both sides


y= (e^x)/(3)


f^(-1)(x)= (e^x)/(3)

User Passy
by
6.4k points